Equilibrium and kinetics of phosphorous adsorption onto bone charcoal from aqueous solution - Ghaneian, Mohammad Taghi (Environmental technology, 2014)
Pyrolysis of fresh sheep bone led to the formation of bone charcoal (BC). The structural characteristics of BC and surface area were determined by X-ray diffraction (XRD) and scanning electron microscopy (SEM). N2 gas adsorption-desorption was analysed by Brunauer-Emmett-Teller isotherm model. The prepared BC was used as an effective sorbent for the removal of phosphate from aqueous solutions. The effect of major parameters, including initial phosphorous concentration, sorbent dosage, pH and temperature, was investigated in this study. Furthermore, adsorption isotherms and kinetics were evaluated. BC was an effective sorbent in phosphate removal from aqueous solution especially in phosphate concentration between 2 and 100 mg/L. The maximum amount of sorption capacity was 30.21 mg/g, which was obtained with 100 mg/L as the initial phosphate concentration and 0.2 g as the sorbent dosage. Best reported pH in this study is 4; in higher pH, adsorption rate decreased dramatically. By increasing the temperature from 20 to 40 degrees C sorption capacity increased; this phenomenon described that adsorption is endothermic. Equilibrium data were analysed by Langmuir, Freundlich and Temkin isotherms. Pseudo first- and second-order and Elovich models were used to determine the kinetics of adsorption in this study. Collected data highly fitted with Freundlich isotherms and pseudo second-order kinetics. Achieved results have shown well the potentiality for the BC to be utilized as a natural sorbent to remove phosphorous from water and wastewater